Comparison of Response Time Database RDBMS with NoSQL on Electronic Medical Records (EMR) - Erwin Apriliyanto (STMIK Sinar Nusantara, 2023)
The electronic medical record is a system for storing and managing patient medical data in electronic form. EMR replaces traditional medical record systems that still use paper, allowing doctors and other medical personnel to access patient medical records more quickly and easily from anywhere, as long as they are connected to the same network. In the EMR, patient medical data is stored in electronic format, such as text, images, and test results. EMR allows doctors to create patient medical records, make drug prescriptions, place laboratory orders and radiology orders, and access other patient medical data in one centralized system. EMR can also enable doctors to perform data analysis to gain insight into a patient's health condition and improve the treatment provided. In this study, the ERM database is used, with one database using PostgreSQL and the other using NoSQL. The purpose of this research is to test the speed performance of PostgreSQL and NoSQL with insert, select, and delete commands. Testing Method Using 1,000 records, 5,000 records, and 10,000 records, with each record being tested three times, and then taking the average, The results of this study are that the NoSQL database insert command has a speed of 3,900 times faster than the PostgreSQL database with 1,000 data records, whereas with 5,000 data records the NoSQL database is 471 times faster, while with 10,000 data records the NoSQL database is 355 times faster, and the select command for 1 NoSQL database table is 8 times faster than the PostgreSQL database, while for the above 1 PostgreSQL database table is faster.